Removal of hexavalent chromium by biochar supported nZVI composite: Batch and fixed-bed column evaluations, mechanisms, and secondary contamination prevention. (February 2019) - Fan, Zixi; Zhang, Qian; Gao, Bin; Li, Meng; Liu, Chaoying; Qiu, Yue
Abstract: Conversion of carcinogenic Cr(VI) to less toxic Cr(III) has long been regarded as the most efficient and effective method to remediate Cr(VI)-contaminated water. However, the widely used reducing agents such as nano zero-valent iron (nZVI) and its derivatives often have low stability and their applications in water treatment may introduce secondary contaminations. To shed light on these, nZVI was loaded on sludge derived biochar to produce nZVI-BC composite for Cr(VI) removal. Batch experiments showed that Cr(VI) adsorption on nZVI-BC was endothermic and highly pH dependent. The adsorption kinetic and isotherm data were described by the pseudo second-order kinetic model and the Langmuir isotherm model, respectively. The removal of Cr(VI) by nZVI-BC was mainly through reduction-adsorption. After the experiment, nZVI-BC was transformed into a stable magnetic adsorbent that can be magnetically separated from aqueous phase during first circle application. In fix-bed columns, nZVI-BC also effectively removed Cr(VI) under various operation conditions and the Thomas and Yoon-Nelson models described the experimental breakthrough curves well. The post-adsorption nZVI-BC was re-pyrolyzed, which stabilized and reduced the bioavailability of Cr in the biochar. Re-pyrolysis thus can be used as an effective technology to reduce the environmental risks of post-adsorbent biochar for safe disposal. Graphical abstract: Highlights: nZVI-BC was successfully synthesized by immobilized nZVI particles on sludge derived biochar. nZVI-BC effectively removed aqueous Cr(VI) through simultaneous reduction and adsorption. nZVI-BC was transformed into a magnetic material during Cr(VI) removal. nZVI-BC in fixed-bed columns effectively removed Cr(VI) under various operation conditions. Re-pyrolysis of post-adsorption nZVI-BC stabilized and reduced the bioavailability of Cr.